Chalcogenia rejzeki sp. nov. from Kenya (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2021)
Chalcogenia rejzeki sp. nov. from Kenya is described, illustrated and compared with the most similar species, and attributed to the Chalcogenia sulcipennis species-group within the genus Chalcogenia Saunders 1871. Brief catalogue of the genus Chalcogenia with new country records is provided.